Multiple cystic lesions after treatment for pulmonary cryptococcosis - Tomoyo Taketa (Wiley, 2021)
Abstract Pulmonary cryptococcosis presents various radiological manifestations depending on the immunological status of the host. The most common chest radiographic findings include single or multiple nodules. Herein, we present a rare case of pulmonary cryptococcosis in a patient with rheumatoid arthritis presenting as multiple cystic lesions that enlarged after treatment.